Avaliação da impedância intraluminal da faringe após exposição ácida em pacientes com laringite posterior - Coutinho, Tanila Aguiar Andrade (2015)
The integrity of the esophageal mucosal barrier is a protective mechanism against gastroesophageal reflux. The baseline value of intraluminal impedance has be used to assess the integrity of the esophageal mucosa. Patients with higher esophageal acid exposure time present lower basal impedance, which leads to structural changes in the mucosa. This study hypothesis is that patients with unspecified chronic laryngopharyngitis have lower basal pharyngeal impedance than healthy individuals after acid exposure. Quantitative, interventional, and open study comprising two groups of patients: Laryngitis Group (LG) (n=11) with patients presenting chronic intermittent hoarseness and laryngeal edema, and Control Group (CG) (n=10) composed by healthy volunteers. LG underwent clinical assessment (standardized questionnaires) and the two groups underwent functional evaluation (high-resolution manometry and intraluminal impedance-pH monitoring). The intervention lasted 55 minutes, from the 1st to 5th, 30mL of water were administered orally (6mL/minute); 16th to 30th, 60mL of hydrochloric acid were administered (2mL/30 seconds); 41st to 45th, 30mL of water were once again administered (6mL/minute). Intraluminal impedance was continuously monitored with a probe whose sensors were placed 2cm above the proximal edge of the upper esophageal sphincter (UES), the edge of the UES, and the proximal esophagus. Values were measured every 5 minutes on stable, artifacts-free segments. Basal impedance 2cm above the upper edge of the UES in laryngitis group was similar to the control (LG=2525±448 vs. CG=2439±282, p=0.72). During acid exposure, 20th minute of the intervention, the impedance was significantly lower in the laryngitis than in control group (LG=1374±334 vs. CG=2595±2110, p=0.02). At the end of the test, 55th minute, this significance was confirmed even after water intake (LG=1088±331 vs. CG=1691±654, p=0.02). In the hypopharyngeal, at the edge of the UES, basal impedance presented no differences among the two groups (LG=2583±322 vs. CG=2514±348, p=0.72). During acid exposure, 20th minute, impedance was lower in LG (LG=1207±212 vs. CG=1518±387, p=0.05) and at the end of the test, 55th minute, there was no significant difference, but the impedance value was higher in control than in laryngitis group (LG=1004±240 vs. CG=1288±427, p=0.19). Hypopharyngeal impedance-pH monitoring values after acid exposure were lower in patients with unspecified chronic laryngitis, commonly attributed to reflux disease, than in healthy volunteers.